A Test of the Fiscal Theory of Price Level: Case Study of Nigeria - Tule, Moses K.; Nuruddeen, Usman; Ogundele, Oloruntoba S.; Martins, Apinran O. (International Journal of Economics and Financial Issues, 2019)
The Paper tests the efficacy of fiscal theory of price level in Nigeria using an Auto Regressive Distributive lag (ARDL) model for the period from 2002Q1 to 2017Q4. The study seeks to test the hypothesis that of Leeper (1991) and Sim (1998) that the price level is not independently determined by the monetary authorities, rather it is as a result of the relationship between monetary and fiscal authorities. The Nigerian Federal Government has had to resort to continuous borrowing in order to meet its financial obligations. The size of the fiscal deficit has ballooned which if not controlled could worsen fiscal vulnerability and eventually lead to financial distress. We find that fiscal deficits have a positive and statistically significant effect on inflation in all models estimated, attributed to the high degree of fiscal dominance in Nigeria. Giving our findings, Nigerian economy needs to address the challenge of high fiscal imbalances. Keywords: Fiscal Deficits; Inflation; Nigeria. JEL Classifications: E62, H620 DOI: https://doi.org/10.32479/ijefi.8768